O desafio da educação infantil : um olhar sobre a formação continuada - Rabelo, Viviani Darolt (2017)
The present study has as aim to organize and to develop with Physical Education teachers of the Municipal Schools of Cuiabá a proposal of continuing formation to the early Childhood Education, from the content expected in the Curriculum Matrix of Reference to the early Childhood Education (4 and 5 years), searching alternatives to improve the school pedagogical practices. Therefore, we did a bibliographic survey about the following axes: teacher formation and formation of Physical Education teachers, the teacher and his continuing formation, the Physical Education and the needs to act in the early Childhood Education, besides treating the childhood in a historical perspective, relating the child to the school, to playing and to the subject of Physical Education in the early Childhood Education. It is a study of the descriptive kind with a qualitative approach, in an universe of 69 schools and 18 Municipal Centers of early Childhood Education (hereby CMEI) and 2 Emergencies Centers of early Childhood Education (hereby CEEI), located in Cuiabá/MT. The subjects were 74 teachers acting in early Childhood Education (4 and 5 years) in the respective schools, CEEI’s and CMEI’s. The methodology chosen was action-research, that is a way of generating new knowledge from the own action of the teacher in the field of work, reflecting about the aspects risen by the own group of teachers, with the intent of transforming the reality of the school where he is a teacher. The tools of data gathering were the documental analysis of the references of the Municipal Secretary of Education of Cuiabá/MT, a initial questionnaire with open and closed questions, a directed interview to the teachers after 14 meetings of study, a final questionnaire in the end of the research as a way of evaluation the formation and, as being a qualitative research, the data gathered, besides the mentioned documents, were notes of the field notebook, photographs, videos, lesson planning notebooks, among other that came during the processes, always looking to respect the way these documents were registered. Regarding the profile of the participant teachers, we identified a meaningful number of licensed teachers in public institutions of teaching, part of them has already done any post-graduation course however a small percentage was directed to early Childhood Education. We also noted that most teachers act less than a year in early Childhood Education. About the importance of the continuing formation, a great number of teachers consider it as important to improve the pedagogical practice or to the professional acting, however they feel the need to study the specific knowledge of early Childhood Education. Connecting the study to the aims and to the content of Physical Education with the early Childhood Education, we noted that a greater group of teachers distinguish aims and content, knowing how to define them, nonetheless a smaller group, but considerable, confuses both, not knowing how to identify them or to use them in the practice of the age range. Ergo it is essential to rethink and reorganize the formations to the acting of the early Childhood Education, relating the proposals in the documents that guide the curricular organization, the aims and contents to this age range, as well as the role of Physical Education in the reality of early Childhood Education.